The Use of Thematic Progression in Writing Hortatory Exposition Text - Linda, Linda; Maisa, Maisa; Mulatsih, Devi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
The research entitled in “The Use of Thematic Progression in Writing Hortatory Exposition Text” is aimed at finding out the students’ activities in learning hortatory exposition text by using thematic progression patterns and finding out the level of students’ writing skill by using thematic progression patterns in learning hortatory exposition text. This research is expected to give contribution and some informations about the implementation of thematic progression patterns  in writing field, especially in hortatory exposition text. Thematic progression is a way to make a good text in term of good cohesion and coherent of text. It means that thematic progression will influence a content of text and it can be organized into a good organization of essay. There are three patterns of thematic progression used namely constant theme, linear theme, and split rheme. The result of this research shows that the use of thematic progression patterns in writing hortatory exposition text was effective. It can be shown by comparing result of pretest and posttest of exeperimental class. The average of pretest was 49,09 while the average of posttest was 76,16. It means that the students’ writing ability in posttest was improved than the pretest.  Based on the students’ documents in post-test of the experimental class, it can be summarized that most of students got the medium and high level. The medium level was the most achieved level with 84%, while the high level was 10%, and low level was 6%. In addition, most of students could pass the KKM (Kriteria Ketuntasan Minimal). Since The KKM for English in Senior High School is 75.Keywords: Hortatory text, Theme, Rheme, Thematic Progression